ACSM technical papers - American Congress on Surveying and Mapping; American Society for Photogrammetry and Remote Sensing; ACSM/ASPRS Convention & Exposition (Bethesda, MD American Society for Photogrammetry and Remote Sensing and American Congress on Surveying and Mapping, 1993)
Annual
Papers for 1993 issued in 3 parts, each with separate title page.
Vols. for 1993-are for the 53rd-ACSM Annual Convention and the 59th- ASPRS Annual Convention.
Keywords: Photogrammetry -- Congresses; Cartography -- Congresses; Photogrammetry -- United States -- Congresses; Remote sensing -- United States -- Congresses; Surveying -- Congresses